Effect of diesel detergent synergists on VOCs emissions from engine - Wei Hongyuan; Yin Zenghui; Wang Shan; Jing Xiaojun; Wu Chunling; Qin Mingcong; Liu Jixu (E3S Web of Conferences, 2022)
In this study, the volatile organic compounds (VOCs) emissions from engine fueled diesel with and without detergent synergist were measured by gas chromatography mass spectrometry(GC-MS). The test results show that compared with reference diesel fuel (without diesel detergent synergist), the use of different diesel detergent synergists has different effects on the VOCs emissions while without after-treatment device. Whether with or without after-treatment device, alkanes always account for the highest proportion of VOCs emissions while engine fuels with different diesel detergent synergists. After-treatment device diesel oxidation catalyst coupled with diesel particulate filter (DOC+DPF) has high catalytic efficiency for VOCs emissions from engine fueled with different fuels, and most of the catalytic efficiency could reach more than 95%. With the catalytic treatment of after-treatment device,the concentrations of carcinogens (detected in this study) in VOCs emissions from engine fueled with and without detergent synergist are far lower than that specified in reference standard GBZ 2.1-2007 “Occupational Exposure Limits for Hazardous Factors in the Workplace and Chemical Hazardous Factors”, respectively. The test results indicate that the use of diesel detergent synergist will not have an adverse impact on human health and it can be safely used.